Warfarin versus non-vitamin k anticoagulants and risk of dementia in patients with atrial fibrillation: a systematic review and meta-analysis - Catarina Luísa Tavares Oliveira (2022)
Background: Atrial fibrillation (AF) is the most common arrythmia in the world amongst the elderly, known for its ability to cause thromboembolic events that can ultimately cause dementia. Studies have proved the benefit of using oral anticoagulants (OACs) to reduce such events. Non-vitamin k anticoagulants (NVKAs), namely, apixaban, dabigatran, rivaroxaban, edoxaban came up last decade as an alternative to vitamin k anticoagulants (VKAs), mainly warfarin, however, its role in preventing dementia comparing to the firsts, is still uncertain. Methods: This systematic review included studies of patients diagnosed with AF, independently of age and sex, medicated daily with OACs, which compared the risk of the dichotomous outcome of dementia, according to the elected OAC, warfarin or NVKAs. Studies that didn't fulfill this purpose were excluded. Pubmed, Web of Science and Scopus were the electronic databases assigned for the literature search that was completed February 12th of 2022, without restrictions of language, year, and follow-up period. The Newcastle Ottawa Scale was used to assess bias risk and additionally, hazard ratios (HR) with 95% confidence intervals (CI) were extracted and pooled estimates were calculated using the random effects model. Results: Nine retrospective cohorts englobing 919932 patients were included in the metanalysis. NVKAs were associated with a decreased risk of dementia comparing with patients treated with warfarin (HR 0.86, CI 0.78-0.95, I2 80%). A sensitivity analysis was performed obtaining a similar effect. Cognitive impairment was a secondary outcome englobing two studies implying a decrease in the risk of such endpoint in patients treated with NVKAs comparing with warfarin. Conclusion: NVKAs contribute to a decreased risk of dementia in comparison with warfarin. Although the favorable results on NVKAs consumption it is important additional studies with longer follow up periods so as randomized control trials which provide more valid data.